PERANCANGAN VIDEO BERBASIS YOUTUBE SEBAGAI MEDIA PEMBELAJARAN PAI - Fauzi Noor Rahman; Agus Fakhruddin (Taklim : Jurnal Pendidikan Agama Islam, 2021)
Improving the quality of learning is one of the efforts that can be made to improve the quality of education. In carrying out these efforts, it must be in line with the times. One of the fairly rapid developments occurred in the field of information and communication technology which penetrated into the world of education. Educators, especially teachers, are required to have high creativity to utilize technology in the learning process, especially in PAI learning. Thus, students should be able to easily communicate and receive knowledge transfer to be able to understand deeply about the PAI material being taught. However, in reality, the lack of interest and enthusiasm of students, especially for PAI material, the actualization of PAI in schools is only 3 hours of lessons a week and PAI teachers are still less able to utilize information and communication technology that is developing in today's era, especially internet technology. This study aims to find alternative solutions in utilizing information technology in the form of the internet, especially YouTube social media for PAI learning. The researcher used descriptive analytical method in this study where the researcher became the key instrument. Data collection techniques using literature study and study of visual materials. Analysis of research data using the theory of multimedia creation and content analysis or content analysis. The results of the first study show that with PAI learning videos uploaded on YouTube social media, students can watch or listen to PAI materials anywhere and anytime. Then the results of the second study, based on various responses on YouTube social media, namely that students are more interested in listening to or watching videos containing material within the scope of aqidah and morality, meaning that students are easier to understand material that is easily digested by them. In addition, in terms of the types of videos presented, students are also more interested in listening to animated videos and illustrations that are very familiar with the world of teenagers and more illustrations that are relevant to the realities of everyday life so that students are more likely to listen to PAI material. or Islamic religion.Keywords: Learning Videos, PAI Materials, YouTube.